Appri’s and Brazil’s new regulatory model: New features and challenges of the dispute settlement clause in ACFI’s - de Galiza Fernandes Luppi, Dávila Teresa (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The purpose of this article is to look at the formation process of the Agreements for the Promotion and Reciprocal Protection of Foreign Investments (APPRIs), comparing them with the new model of the Investment Cooperation and Facilitation Agreement (ACFI) created by Brazil in 2015, especially with regard to the peculiarities of the dispute settlement clause. The ACFI, as an alternative model in the scenario of reforms to the traditional international investment protection system, prioritised institutional governance mechanisms for cooperation and dispute resolution, focusing on dispute prevention bodies and excluding investor-state arbitration. The question is whether this choice represents progress or an anachronism in the current panorama of International Investment Law.